2019
DOI: 10.1371/journal.pone.0221482
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of mTORC1 signaling induced by biallelic loss-of-function mutations in SZT2 underlies a discernible neurodevelopmental disease

Abstract: There have been increasing number of reports of SZT2 -related neurological diseases, the main symptoms of which are epilepsy, developmental delay, macrocephaly and a dysmorphic corpus callosum. SZT2 functions as a regulator of mechanistic target of rapamycin complex 1 (mTORC1) signaling in cultured human cell lines and mouse tissues. However, it remains to be determined whether mutations in SZT2 in human patients alter mTORC1 signaling. In this study, we aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…SZT2 loss‐of‐function variants alter the mechanistic target of rapamycin (mTOR) signalling 7 . This may explain the role of its variants in epileptogenesis 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SZT2 loss‐of‐function variants alter the mechanistic target of rapamycin (mTOR) signalling 7 . This may explain the role of its variants in epileptogenesis 1 .…”
Section: Discussionmentioning
confidence: 99%
“…SZT2 loss-of-function variants alter the mechanistic target of rapamycin (mTOR) signalling. 7 This may explain the role of its variants in epileptogenesis. 1 It was recently shown that SZT2 dysfunction leads to a hyperactivation of the mTORC1 signaling pathway resulting in increased cell proliferation, disturbed connectivity of the brain and epileptogenesis.…”
mentioning
confidence: 97%
“…Nakamura Y et al recently examined mTORC1 activity in lymphoblastoid cell lines (LCLs) from affected individuals 24 . They report elevated mTORC1 activity in cell lines derived from individuals with biallelic SZT2 variants relative to cell lines generated from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…KPTN functions in a protein complex (KICSTOR) negatively regulating mTOR activity in response to nutrient availability 19,33 . Given the known contribution of mTOR pathway members in numerous brain overgrowth disorders in humans 9,[63][64][65] , this provides a plausible mechanism for KRD overgrowth.…”
Section: Kptn Regulates Mtor Signalling In Vivomentioning
confidence: 99%
“…Aberrant mTOR signalling is associated with numerous diseases such as cancer, diabetes, and neurological disorders including epilepsy, autism, developmental delay and macrocephaly [10][11][12][13] . De novo and inherited variants have been identified in numerous mTOR pathway genes, leading to the term "mTORopathies" to describe the involvement of the mTORC1 signalling pathway in these disorders [15][16][17][18][19][20] . A growing body of literature is uncovering the intricate relationship between the mTOR pathway, neural stem cell proliferation, and neuronal differentiation [21][22][23][24] , providing insights into the mechanisms of malformations of cortical development such as tuberous sclerosis complex, focal cortical dysplasia, hemimegalencephaly, and megalencephaly [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%